ESTIMATION OF CHANGES IN MANGROVE CARBON STOCKS FROM REMOTELY SENSED DATA-BASED MODELS: CASE STUDY IN QUANG YEN TOWN, QUANG NINH PROVINCE DURING 2017 - 2019 - Hai Hoa, Nguyen; Huu Nghia, Nguyen (Journal of Forestry Science and Technology, 2019)
Mangroves or tide-dominated mangroves are found along shallow shorelines with modest slope where they receive freshwater runoff and nutrients from rainfall. They have been globally recognised as their vital functions in preventing coastal erosion, mitigating effects of wave actions and protecting coastal habitats and adjacent shoreline land-uses from extreme coastal events. By using Sentinel 2A imageries, the study has constructed the spatial ditribution of mangrove forests in 2017 and 2019. The accuracy evaluation showed that the overall accuracy of the 2019 Sentinel classification was 89.0%, while accuracy assessments of 2017 Sentinel image also was 87.7% overall accuracy. There were 1822.9 ha of mangrove forests in March 2019, 2476.1 ha in December 2017. The AGB and C stocks of mangrove forests in Quang Yen has changed over time. There were small variations of AGB and C stocks of mangrove forests between field measurements and Sentinel-based estimation in 2019. Therefore, the study highly suggests that using Sentinel imageries to estimate AGB and C stocks of mangrove forests is reliable and applicable to Quang Ninh coast and it should be expanded in other similar coastal areas in Quang Ninh province.